2018
DOI: 10.1093/milmed/usy198
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcus Outbreak in a Canadian Armed Forces Training Facility

Abstract: Between December 2016 and April 2017, two cases of invasive Group A Streptococcus (GAS) infections were reported at a Canadian military training facility. An outbreak was declared and a field investigation was launched to characterize the outbreak and identify associated risk factors to limit transmission. Throat culture data from military personnel at the garrison were analyzed. Investigators tracked invasive GAS cases and non-invasive hospitalized GAS cases, and conducted site visits and case interviews. Sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…A comparable study conducted in Canada also reported similar findings [62]. Hammond-Collins et al [49] also conducted a study on GAS-infected cases between August 2016 to January 2018 in Belgium. The results showed incidence rates of 2333/100,000 persons in homeless groups and 25/100,000 persons in non-homeless groups, showing a higher incidence (100 times higher) for homeless persons compared to non-homeless persons.…”
Section: Common Areas Of Infectionsupporting
confidence: 53%
See 3 more Smart Citations
“…A comparable study conducted in Canada also reported similar findings [62]. Hammond-Collins et al [49] also conducted a study on GAS-infected cases between August 2016 to January 2018 in Belgium. The results showed incidence rates of 2333/100,000 persons in homeless groups and 25/100,000 persons in non-homeless groups, showing a higher incidence (100 times higher) for homeless persons compared to non-homeless persons.…”
Section: Common Areas Of Infectionsupporting
confidence: 53%
“…The common environments for GAS infections included schools, nurseries and kindergartens [16,36,37], hospitals [33,34,[38][39][40][41], homeless shelters [22,50], care homes [38,[42][43][44][45][46][47][48] and military training facilities [49].…”
Section: Common Environments Of Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Both acute and chronic forms of GAS can be seen at the age of three and over; therefore, they are diseases that frequently occur in a wide age group. [14] Contagion occurs with close contact through infected droplets. In addition to domestic transmission, other environments with a high risk of transmission include public areas, such as schools, barracks, and kindergartens.…”
Section: Resultsmentioning
confidence: 99%